Employer Attractiveness, Work Expectations, Corporate Reputation dan Person-Organization Fit terhadap Intention to Apply - Laras Kusuma Astuti; Yulyanti Fahruna; Mazayatul Mufrihah; Ahmad Shalahuddin; Ikram Yakin (Forum Kerjasama Pendidikan Tinggi, 2025)
BUMN Banking faces competition in obtaining potential job candidates from Generation Z with work preferences different from those of previous generations. The study sought to assess the effects of employer attractiveness and work expectations on the intention to apply for jobs at BUMN Banking from graduates in West Kalimantan, utilizing corporate reputation and person-organization fit as mediating variables. With data collected via questionnaires from 256 respondents, the study's results indicate that employer attractiveness, work expectations, corporate reputation, and person-organization fit positively and significantly impact the desire of Generation Z at BUMN Banking. Additionally, corporate reputation and person-organization fit can mediate the link between employer attractiveness and intention to apply at BUMN Banking. However, a person-organization fit cannot mediate the impact of work expectations regarding the intention to apply at BUMN Banking.